2023
DOI: 10.3389/fpubh.2023.1113550
|View full text |Cite
|
Sign up to set email alerts
|

Equity dimensions in initiatives promoting urban health and wellbeing in east and southern Africa

Abstract: Urbanisation in east and southern Africa (ESA) has brought opportunity and wealth together with multiple dimensions of deprivation. Less well documented in published literature on the ESA region are features of urban practice that promote health equity. This work thus aimed to explore features of urban initiatives aimed at improving health and wellbeing in ESA countries and their contribution to different dimensions of health equity. A thematic analysis was implemented on evidence gathered from 52 documents fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…These studies, among others, illustrate the factors affecting urban economic development in South Africa as it works towards achieving sustainable urban development. Moreover, research on solutions to rapid urbanization in South Africa has focused on curbing immigration, investing in rural areas [6,9,13,28], policy development and improved governance, and spatial inclusivity [57,62,67]. Recent studies have also focused on technology and innovation [58,77,79], and on social investment [65,70,73,74] as an alternative approach to various aspects of socio-economic and urban development.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These studies, among others, illustrate the factors affecting urban economic development in South Africa as it works towards achieving sustainable urban development. Moreover, research on solutions to rapid urbanization in South Africa has focused on curbing immigration, investing in rural areas [6,9,13,28], policy development and improved governance, and spatial inclusivity [57,62,67]. Recent studies have also focused on technology and innovation [58,77,79], and on social investment [65,70,73,74] as an alternative approach to various aspects of socio-economic and urban development.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, Bandauko and Arku argue that the adoption of smart-city ideas in Africa must be rooted in contextual realities and properly designed to create urban spaces that are sustainable and inclusive [58]. For instance, a study by Loewenson, Mhlanga, Gotto, Chayikosa, Goma, and Walyaro [62] reported potential gains in urban development attained by focusing on low-income communities; links between social, economic, and ecological benefits; and investment in women and young people, as well as urban biodiversity. This implies that the entire value chain of urban development, whether within formal or informal dimensions, must be considered to optimize planning, enable economic growth, and improve the sustainability of the required resources.…”
Section: Strategies To Accelerate Sustainable Urban Development 421 W...mentioning
confidence: 99%
See 1 more Smart Citation
“…It is for these reasons that Bandauko and Arku argue that the adoption of smart city ideas in Africa must be rooted in contextual realities and properly designed to create urban spaces that are sustainable and inclusive. For instance, a study by Loewenson, Mhlanga, Gotto, Chayikosa, Goma and Walyaro [59] reported potential gains in urban development by focusing on low-income communities, links between social, economic, and ecological benefits, and investment in women and young people as well as urban biodiversity. This implies that the entire value chain whether from formal or informal dimensions must be considered to optimize planning, enable economic growth, and improve the sustainability of the resources required.…”
Section: Working With Informality and Not Against Itmentioning
confidence: 99%
“…Urbanization is projected to reach 62% of the population across sub-Saharan Africa by 2050 ( 1 ). Interventions have been initiated to address urban stress, deprivation, and structural inequities but most face contextual, socio-political, institutional, and resource challenges ( 2 ). Inadequacies in water, sanitation and hygiene (WASH) facilities in living and working environments and related exposure to health hazards is a major consideration ( 3 ).…”
Section: Introductionmentioning
confidence: 99%